Low depression literacy exacerbates the development and progression of depressive mood in Chinese adult social media users during COVID-19: A 3-month observational online questionnaire-based study with multiple cross-sectional analyses - Dan Shan; Shaoyang Li; Ruichen Xu; Jingtao Huang; Yi Wang; Yuandian Zheng; Shanshan Huang; Yuming Song; Junchu Han; Sayaka Suto; Zhihao Dai (Frontiers Media S.A., 2023)
BackgroundThe main purpose of this study was to explore the relationship between depression literacy (D-Lit) and the development and progression of depressive mood.MethodsThis longitudinal study with multiple cross-sectional analyses used data from a nationwide online questionnaire administered via the Wen Juan Xing survey platform. Eligible participants were 18 years or older and had subjectively experienced mild depressive moods at the time of their initial enrollment in the study. The follow-up time was 3 months. Spearman's rank correlation test was used to analyze the predictive role of D-Lit on the later development of depressive mood.ResultsWe included 488 individuals with mild depressive moods. No statistically significant correlation between D-Lit and Zung Self-rating Depression Scale (SDS) at baseline was observed (adjusted rho = 0.001, p = 0.974). However, after 1 month (adjusted rho = −0.449, p < 0.001) and after 3 months (adjusted rho = −0.759, p < 0.001), D-Lit was significantly and negatively correlated with SDS.LimitationsThe targeted subjects were limited to the Chinese adult social media users; meanwhile, China's current management policies for COVID-19 differ from most of the other countries, limiting the generalizability of this study.ConclusionDespite the limitations, our study provided novel evidence supporting that low depression literacy may be associated with exacerbated development and progression of depressive mood, which, if not appropriately and promptly controlled, may ultimately lead to depression. In the future, we encourage further research to explore the practical and efficient ways to enhance public depression literacy.